Frontiers of monkeypox research: An analysis from the top 100 most influential articles in the field - Xuhao Li; Yang Li; Wenyan Yu; Zhixia Jia; Jinling Li; Yuanxiang Liu; Jiguo Yang (Heliyon, 2023)
Background: Monkeypox (MPX) has made recurrence after decades as a neglected zoonotic disease. More nations have reported endemic monkeypox in the past decade than in the previous forty. The World Health Organization has warned that the world may face another significant challenge after dealing with COVID-19, a pandemic, and the Monkeypox outbreak. Early appraisal of monkeypox research and development allows researchers to anticipate solutions for large outbreaks. We conducted a bibliometric analysis of this study's top 100 cited papers to identify regional research patterns. Methods: Our method was to search the SCI-Expanded database on Web of Science (WOS) for the top 100 papers that were cited in MPX on this database. We examined relevant literature from different years, journals, countries/regions, institutions, authors, and keywords.In order to create knowledge maps, we used the programs VOSviewer, Citespace, Scimago Graphica and the bibliometric online analysis platform. After compiling the relevant literature in Excel, we could estimate the field's focus and trends. Results: A total of 47 journals from 36 countries and regions published the top 100 cited papers between 1999 and 2023. The majority of articles were published in EMERGING INFECTIOUS DISEASES, while the highest average number of citations per paper were found in the NEW ENGLAND JOURNAL OF MEDICINE. The UNITED STATES contributed the most publications, followed by ENGLAND and SWITZERLAND. As far as the total number of publications goes, the Centers for Disease Control & Prevention in the USA, the National Institute of Health in the USA, and the World Health Organization each contributed the most papers. The major categories are immunology, virology and infectious diseases. The top five keywords were infection, Congo, virus, smallpox, and transmission. The cluster analysis suggests MPX research will focus on safe and effective vaccines and epidemic prevention. Conclusion: By using bibliometric analysis, MPX researchers can quickly and visually identify their research focus and boundaries. Although studies suggest that antiviral medicine is the best treatment, creating an effective vaccine might lessen and avoid MPX pandemics in the long term. Our findings imply that safe and effective vaccines may be the focus and trends for future MPX research. International coordination for case monitoring and identification is essential to understand monkeypox disease's ever-changing epidemiology.